The evolution of superbugs in space: a genomic perspective on pathogens in the International Space Station environment - Sara Pearl; Hithesh Kumar; Santhiya Vijayakumar; Soumya Basu; Sudha Ramaiah; Anand Anbarasu (Journal of Genetic Engineering and Biotechnology)
Microgravity, pressure, and temperature variations in the International Space Station (ISS) create conditions leading to the emergence of superbugs. Due to technical issues in spacecraft, astronauts are forced to stay in ISS for extended periods; prolonged stay and exposure in stressful ISS environment weakens their immune systems, increasing susceptibility to infections. The presence of hypervirulent and antibiotic-resistant pathogens in space station is a worrisome feature as these might cause serious life-threatening infections in astronauts staying in high stress environments with weakened immune systems. In the present study, we compared antimicrobial resistance genes (ARGs) and virulence factors (VFs) in bacterial genomes from ISS with Earth counterparts. ISS genomes exhibited elevated counts of defense-related genes, particularly in E. ludwigii and E. cancerogenus. Among genes uniquely found in ISS genomes, CRISPR-Cas system components were notably prevalent. Though Earth genomes harbored higher number of ARGs overall, several species from ISS possessed modestly higher ARG counts. VFs profiling showed a slightly lower count in ISS genomes, but P. conspicua, E. ludwigii, and K. pneumoniae from ISS carried exclusive VFs linked to metal ion uptake and secretion systems, suggesting environment-driven functional adaptations. The adaptation of pathogenic bacteria in ISS is alarming and therefore periodic monitoring of bacterial genomic surveillance is important. Our findings shed light on genomic profiles in bacterial strains from both ISS and Earth, enhancing our understanding of the bacterial pathogens’ potential impact on drug resistance and pathogenicity in space-missions and the possible threat of spread from ISS.